Research progress on the regulatory mechanism of probiotics on animal intestinal health - HAO Zhuang; DING Xuedong; WANG Jing (浙江大学学报. 农业与生命科学版)
Probiotics are a class of microorganisms that are beneficial to the health of the host, possessing the roles such as enhancing animal growth performance and improving intestinal health. In the context of a comprehensive ban on the use of growth-promoting antibiotics in animal husbandry, probiotic feed additives can serve as alternatives to antibiotics and provide robust support for health breeding. In this paper, we reviewed the possible mechanisms by which probiotics regulate animal intestinal health. We focused on the digestion and absorption of intestinal nutrients, microbial barrier, chemical barrier, physical barrier and immune barrier, to provide a theoretical basis for the application of probiotics.